Correlation between real geometry and tensile mechanical behaviour for Ti6Al4V electron beam melted thin specimens. (June 2020) - Sepe, R.; Franchitti, S.; Borrelli, R.; Di Caprio, F.; Armentani, E.; Caputo, F.
Highlights: Surface morphology and tensile properties are affected by the specimen size. Measured and effective areas difference decreases as the specimen thickness increases. Considering specimen effective area, mechanical properties tend to literature data. Abstract: The Electron Beam Melting (EBM) is an Additive Layer Manufacturing (ALM) technique used to directly manufacture 3D functional parts from metal powder, selectively melted, layer by layer, by an electron beam according to a geometry defined by a CAD model. The EBM technology allows benefitting from countless advantages: material waste reduction, easy manufacturing of complex shapes, lead time reduction, etc; on the other hand the EBM process is typically associated with lower resolutions and higher surface roughness ( Ra  = 25–30 μm) compared to similar laser based powder bed metal processes. Therefore the surface morphology may be a critical issue for the structural integrity of components made in EBM and used in-service in their "as built" condition, i.e. with the characteristic surface released by the process. This study evaluates surface morphology and tensile properties of Ti6Al4V specimens of varying nominal thickness (1–5.0 mm), made by using EBM process with a layer thickness of 50 μm. The aim is therefore to investigate how the surface morphology and the tensile properties are affected by the nominal thickness of the component.